Filsafat Manusia dalam Bhagavad Gita - Ni Wayan Sumertini (Sanjiwani: Jurnal Filsafat, 2021)
Humans want to know about the origin, fate, freedom, purpose of life, and the meaning of life. Human philosophy is an analysis of the discussion of the human self from a philosophical point of view. In Hinduism man is not only about the body, but also about the soul. In Hinduism, the body has a layer called Tri Sarira. Tri Sarira consists of sthula sarira (gross body), Suksma Sarira (subtle body), and Antah Karana Sarira (causative body). Sthula Sarira or gross body, is an observable and visible body that can directly interact with society and the environment. This gross body is formed by gross elements, which have visible and form. Suksma Sarira or subtle body is a body consisting of subtle elements, such as mind, intelligence, consciousness, divinity, and the faculties. Antah Karana Sarira or causative body, is the spirit or ātma which gives life to the body so that the body can carry out activities. Body and spirit need each other, the spirit needs the body for karma, while the body needs the spirit to live. The essence of human being born is to learn. Is one way of controlling the mind and focusing the mind on God so that the mind is not carried away by the senses which results in attachment. Paramātma is the spirit that accompanies ātma in each of his incarnations, while ātma is the soul bound by karma.